Caring behaviour and quality of life patients with hemodialysis at Baiturrahim Hospital Jambi - Sari, Mila Triana; Putri, Miko Eka; Fajri, Jufri Al; Daryanto, Daryanto; Listautin, Listautin; Fahkrunisa, Lulu (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background: Hemodialysis is one of therapy in chronic renal failure. It’s changed aspects of vitality, physical functional, and psychological and so that affected to quality of life. How caring behaviour were correlated to quality of life was unclear. This reasearch to analyse correlation between caring behaviour to quality of life of patients with chronich renal failure. Method: This research was a quantitative design with Cross Sectional approached. As sums 93 of 122 of subjects has recruited as sampling purpossive. Its conducts on November 2022 to July 2023 at Baiturrahim Hospital, Jambi. Data collected by means Caring Dimension Inventory-25 and KDQOL. Data were analysed and presented as univariate and bivariate with Sperman Rho test at significance level < 0,05. Results: As much of 62,4% subjects reports were good caring bahaviour, and 59,1% subjects were good quality of life. Nurse caring behaviour were correlated with quality of life of patients with hemodialysis. This study implicated that caring behaviour were important attitudes in nusing care for patients undertook hemodialysis. Conclusion: Caring behaviour Nurse were needed to improve the patients quality of life. Nurse who taking care of patients supposed to show how to practice Caring behaviour.